1996
DOI: 10.2337/diab.45.6.818
|View full text |Cite
|
Sign up to set email alerts
|

Differential Responsiveness to Interferon-α in β-Cells and Non-β-Cells

Abstract: Interferon-alpha (IFN-alpha) is important in the innate immune defense, particularly in viral infections. IFN-alpha induces 2',5'A synthetase, the products of which, 2',5'-oligoadenine nucleotides, activate mRNA degrading enzymes. IFN-alpha is the first detectable cytokine in the insulitis lesion seen in recent-onset IDDM, and insulin promoter directed expression of IFN-alpha in transgenic mice leads to development of IDDM. Here, we demonstrate that IFN-alpha induces 2',5'A synthetase activity only in insulin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…This can be due to the presence of subpopulations of ␤ cells in islets or to the metabolic heterogeneity of these cells (35). In addition, a heterogeneous susceptibility of ␤ cells to the effects of IFN-␣ could play a role; indeed, it has been reported that there is a differential response to IFN-␣ in islet cells in a rat model (4). Further experiments are needed to clarify the mechanisms of the susceptibility of human islet cells to CVB.…”
Section: Discussionmentioning
confidence: 99%
“…This can be due to the presence of subpopulations of ␤ cells in islets or to the metabolic heterogeneity of these cells (35). In addition, a heterogeneous susceptibility of ␤ cells to the effects of IFN-␣ could play a role; indeed, it has been reported that there is a differential response to IFN-␣ in islet cells in a rat model (4). Further experiments are needed to clarify the mechanisms of the susceptibility of human islet cells to CVB.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Bonnevie-Nielsen and colleagues (36,37) showed that IFN-␣ increases 2-5AS activity in cell extracts from insulin-producing cell lines and rat islet cells. In the present study, we demonstrate that both IFN-␣ and -␥ increase 2-5AS mRNA expression in islet cells, suggesting that the increased expression level of 2-5AS can at least, in part, explain the observations made by Bonnevie-Nielsen et al…”
Section: Discussionmentioning
confidence: 99%
“…Finally, overexpression of IFN- α , with or without poly(I:C), induces apoptosis in beta TC3 cells but not in alpha TC3 cells (Figures 7 and 8). It is unlikely that the observed differences between pancreatic beta and alpha cells are due to use of transformed cell lines, since previously we have observed increased 2′5′AS activity after IFN- α stimulation in primary rat beta cells but not in rat non-beta (mainly alpha) islet cells [17]. The results suggest that pancreatic beta cells have much more intrinsically responsive elements in activation of the 2′5′AS system than alpha cells.…”
Section: Discussionmentioning
confidence: 74%
“…We have shown 2′5′AS activity to be highly induced by IFN- α and poly(I:C) (polyinosinic:polycytidylic acid, a synthetic dsRNA) in insulin-producing RIN rat beta cell lines [15]. Furthermore, we demonstrated that IFN- α sensitivity was not solely a characteristic of cultured cell lines, since it was also present in PBL from diabetes-prone BB rats [16] and in freshly isolated rat islets and rat beta cells [17]. In human islets, other investigators have shown that IFN- α was produced de novo by enterovirus-infected beta cells, but not by enterovirus-infected alpha cells [18].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation